ESTIMASI INTENSITAS UPWELLING PANTAI DARI SATELIT AQUAMODIS DI PERAIRAN SELATAN JAWA DAN BARAT SUMATERA - Dortje Theodora Silubun; Jonson Lumban Gaol; Yuli Naulita (Jurnal Teknologi Perikanan dan Kelautan, 2015)
Monsoonal upwelling generally occurred along the coasts of South Java to Western Sumatera. The aimed of this study was to estimate the upwelling intensity derived from sea surface temperature (SST) and chlorophyll-a. SST and chlorophyll-a data was obtained from 3rd level of Aqua-MODIS satellite censor, and wind data derived from Quikscat satellite censor on July 2002 to June 2011. Upwelling index derived from coastal upwelling index (CUIx) formula. Statistical analysis was used to describe the relationship of SST and chlorophyll-a to CUIx. The result of this study show that the occurrence of upwelling was in east monsoon temporally, the range of SST is about 25.10 – 27.30 °C and chlorophyll-a is about 0.30 – 0.67 mg m-3. However in 2006 the anomaly of upwelling intensity coincide perfectly with the descend of SST to 24.98 °C (Sout Java) and 25.97 °C (West Sumatera), meanwhile the concentration of chlorophyll-a is increase to 1.3 mg m-3 (West Sumatra) and 3.71 mg m-3 (South Java). Statistical analysis show that the SST give a strong relationship between CUIx and SST (r=0.84) in West Sumatera. Meanwhile in South Java, both of those parameters (SST and Chlorophyll-a) gives the strong relationship to CUIx respectively (r= 0.86 and r = 0.81).